A methodological template for the design and evaluation of evidence-based injury prevention fact sheets. (1st March 2011) - Corbett, M; Morrongiello, B; Ward, L
Abstract : In Canada, public health agencies often employ fact sheets or brochures as means of communicating injury prevention messaging to target groups; these are used because they are cost-effective and can reach large segments of the population. Unfortunately, the design of these instruments rarely reflects an evidence-based process, lacks theoretical grounding, and communication effectiveness is rarely assessed. In collaboration with Safe Kids Canada, we devised a methodological template for the development and evaluation of fact sheets targeting parental safety behaviours. This project involved the development of fact sheets targeting parents of infants at two ages (0–6, 6–12 months). The process employed a rigorous program evaluation framework, including a logic model, grounded in social cognitive theories and existing evidence that resulted in a focus on injury-prevention attitudes, self efficacy, and beliefs about vulnerability and severity of infant injury. Focus group testing with parents allowed us to compare the impact of alternative wording and images on cognitions, emotional reactions and parents injury-prevention beliefs and attitudes. Evidence drawn from these focus groups guided the final development of the fact sheets. A report was produced detailing evidence and recommendations as well as the process of developing and evaluating fact sheets, providing a template for future instrument development.